The democratic deficit and European Central Bank crisis monetary policies. Issue 1 (February 2019) - Högenauer, Anna-Lena; Howarth, David
This article presents the argument that European Central Bank (ECB) policy-making from the start of the sovereign debt crisis in 2010 undermined the democratic legitimacy of the ECB. We start with the argument – defended by a number of scholars including Majone and Moravcsik – that where European Union (EU) policy-making is technocratic and does not have significant redistributive implications it can benefit from depoliticization that does not undermine the democratic legitimacy of this policy-making. This is notably the case where EU institutions have narrow mandates and are constrained by super-majoritarian decision-making. Prior to the international financial crisis, the ECB's monetary policies were shaped entirely by the interpretation that its mandate was primarily to ensure low inflation. From the outbreak of the sovereign debt crisis, the ECB adopted a range of policies which pushed its role well beyond that interpretation and engaged in a form of redistribution that directly undermined treaty provisions.